Unhealthy eating and weight dissatisfaction in adolescents who never, occasionally, or regularly use smokeless tobacco (Swedish snus). Issue 7 (29th April 2019) - Reas, Deborah L.; Wisting, Line; Stedal, Kristin; Dahlgren, Camilla Lindvall
Abstract: Objective: Although cigarette smoking has been linked to weight‐related concerns and unhealthy weight control practices, little is known about weight dissatisfaction and eating among adolescents who use smokeless tobacco (SLT) products. The use of Swedish moist snuff (snus) has increased dramatically over recent years, surpassing cigarette smoking among young people in several countries. This study investigated differences in unhealthy eating behaviors and weight dissatisfaction in male and female adolescents who never, occasionally, or regularly use snus. Method: Adolescents aged 16–19 years enrolled in high school (11th, 12th, and 13th grades) completed a cross‐sectional, online survey of adolescent health and well‐being. Meal skipping and snus use frequency were assessed in the total sample ( N  = 23, 622), and items assessing weight dissatisfaction ( n  = 4, 195) and eating‐related pathology ( n  = 3, 563) were administered to subsamples. Analyses were adjusted for cigarette smoking, parental education, and socioeconomic status. Results: Adolescents who used snus, especially on a daily basis, reported less regular breakfast, lunch, and dinner consumption. Females who used snus on an occasional basis reported significantly more disturbed eating pathology. Snus use was associated with weight dissatisfaction in males and females, manifesting differentially according to gender and snus use frequency. Discussion: Unhealthy eating behaviors and weight dissatisfaction were significantly elevated among snus users aged 16–19 years. An increased awareness that occasional snus use may signal disturbed eating pathology among adolescent females is important for detection and prevention efforts. Parents, schools, and health professionals should be vigilant for possible snus use among weight‐dissatisfied adolescents.